2007
DOI: 10.1007/s00411-007-0133-0
|View full text |Cite
|
Sign up to set email alerts
|

Internal dose assessment of 210Po using biokinetic modeling and urinary excretion measurement

Abstract: The mysterious death of Mr. Alexander Litvinenko who was most possibly poisoned by Polonium-210 ( 210 Po) in November 2006 in London attracted the attention of the public to the kinetics, dosimetry and the risk of this high radiotoxic isotope in the human body. In the present paper, the urinary excretion of seven persons who were possibly exposed to traces of 210 Po was monitored. The values measured in the GSF Radioanalytical Laboratory are in the range of natural background concentration. To assess the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
6
0
4
Order By: Relevance
“…95 On the basis of the calculated organ absorbed doses and different assumptions regarding blood absorption and lethal absorbed doses for red bone marrow, kidneys, and liver, the minimum estimated amount of 210 Po which led to the death of A. Litvinenko is estimated to range from 27 to 1,408 MBq, about 0.2 to 8.5 μg, if only 210 Po was used as a poison. 96 These estimations are in agreement with animal data on the effects of 210 Po. 78,92 The data obtained for a number of mammalian species are consistent with death occurring within 20 days of an uptake to blood of about 1−4 MBq/kg.…”
Section: ■ Deterministic Effectssupporting
confidence: 84%
“…95 On the basis of the calculated organ absorbed doses and different assumptions regarding blood absorption and lethal absorbed doses for red bone marrow, kidneys, and liver, the minimum estimated amount of 210 Po which led to the death of A. Litvinenko is estimated to range from 27 to 1,408 MBq, about 0.2 to 8.5 μg, if only 210 Po was used as a poison. 96 These estimations are in agreement with animal data on the effects of 210 Po. 78,92 The data obtained for a number of mammalian species are consistent with death occurring within 20 days of an uptake to blood of about 1−4 MBq/kg.…”
Section: ■ Deterministic Effectssupporting
confidence: 84%
“…Their data showed that for most of the investigated individuals with increased urinary 210 Po excretion, approximately 7 days after consumption, 210 Po excretion was decreased almost to background level. It should be added, however, that such a sharp decline in urinary 210 Po excretion after ingestion does not follow from biokinetic models, as evidenced by Li et al (2008).…”
Section: Methodsmentioning
confidence: 92%
“…Biokinetic and dosimetric models were used to retrospectively estimate the possible intake of radionuclide 210 Po for the ex-Russian spy Alexander Litvinenko. 119)…”
Section: Internal Exposure Monitoringmentioning
confidence: 99%